DEVELOPING PODCAST OF ENGLISH SONG AS LISTENINGMEDIA FOR THE STUDENTS AT THE TENTH GRADE OF SENIOR HIGH SCHOOL - Mutia Puspa Rani (State Institute for Islamic Studies IAIN of Metro, 2015)
Listening is one of the fundamental language skills.Based on the pre survey research, many students at Senior High School have not attractiveness in listening course.This research tried to develop podcast of English song (PES) as the media in order to help the teacher in teaching listening and make the students interested in listening course. The type of the reseach is research development.The steps of this research were self evaluation, expert review and one-to-one, small group, and field test. The subjects of this research are the students of SMA State 3 Metro and SMK Muhammadiyah 3 Metro. The researcher collects the data by giving some questionnaires to the expert review and students whether the media is applicable and suitable or not . The result showed that: first, most of the students felt fun and enjoyable in the learning process of listening course. Second, PES media was applicable, the students were active, very enthusiastic, excited with PES media.